Meningkatkan Efektivitas Pembelajaran Pendidikan Agama Hindu melalui Penggunaan Lembar Kerja Siswa Kelas V SD Negeri 25 Cakranegara - Dewi, Ni Kadek (Lembaga Yasin AlSys, 2021)
The aims of this study are: To determine the effectiveness of learning Hindu Religious Education through the use of the fifth grade student worksheets at SD Negeri 25 Cakranegara in the 2019/2020 academic year. This research was designed using Classroom Action Research. The subjects in this study were the fifth grade students of SD Negeri 25 Cakranegara, totaling 11 people, consisting of 4 female students and 7 male students. While the research procedure goes through the stages of planning, implementing actions, observing, and reflecting. The results showed that the use of Student Worksheets (LKS) could increase the effectiveness of PAH learning for fifth grade students of SD Negeri 25 Cakranegara in the odd semester of the 2019/2020 school year. This shows that the completeness of learning PAH for fifth grade students of SD Negeri 25 Cakranegara in studying PAH material through the use of Student Worksheet Teaching Materials (LKS) in cycle II has reached the target indicator of success in research, namely 100% which has a value above the KKM of 85%. targeted.